Eco-social and behavioural determinants of diarrhoea in under-five children of Nepal: a framework analysis of the existing literature. Issue 1 (December 2016) - Budhathoki, Shyam; Bhattachan, Meika; Yadav, Ajay; Upadhyaya, Pawan; Pokharel, Paras
Abstract Background While diarrhoea is the second major killer among the under-five children in the world with an estimation of 760, 000 deaths annually, it stands as a major killer in Nepal with an annual incidence of 500 per 1000 under-five children with diarrhoea. Diarrhoea is responsible for a wide range of morbidity and mortality among children in Nepal. The objective of this review work is to identify the eco-social and behavioural determinants of diarrhoea among the under-five children of Nepal. Methods A literature review was conducted using the Dahlgren and Whitehead model (1991) between June and October 2015. PubMed, Nepal Journals online and Google Scholar were used to search for literature published between 1989 and July 2015 using defined keywords. Results Children of age group 6–23 months are at higher risk, as supplementary diets are introduced to the children from the age of 6 months. Male children have better access to healthcare services. Malnourished children also have a higher chance of developing persistent diarrhoea. Provision of safe water and sanitation has direct link with the prevention and control of diarrhoea. Male gender with high income positively influences the treatment-seeking behaviour. Mother's education and hand-washing practice have direct influence in child health. Hand-washing practices with soap which are protective are influenced by the cultural beliefs. Involvement of community health volunteers increases the access to the health system, thereby reducing the diarrhoeal burden in the community. Conclusion Age, gender, hand-washing behaviour, nutritional status of children, education of mothers, water and sanitation, healthcare services, cultural and societal values and income of the household were identified determinants for diarrhoea in under-five children of Nepal.